2007
DOI: 10.1017/s0007114507832879
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and Infection: An Update

Abstract: The original Scrimshaw, Taylor and Gordon conceptual framework for the interaction of nutrition and infection has well served the scientific community for almost half a century. At its core is the notion of synergistic (mutually reinforcing) and antagonistic (mutually nullifying) influences of the malnourished state on infectious conditions and vice versa. Research on a series of advancing fronts, however, has allowed the incorporation of both relevant public health issues (parasitosis, emerging infectious dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 57 publications
(62 reference statements)
0
44
1
3
Order By: Relevance
“…The result of a study by Solomon (2007) showed that anemic pregnant women is four times at risk for delivering premature infants and 1.9 times at risk for delivering infants with low birth weight, compare to non anemic pregnant women.…”
Section: The Effect Of Nutritional Status Of Pregnant Women Toward Lomentioning
confidence: 99%
“…The result of a study by Solomon (2007) showed that anemic pregnant women is four times at risk for delivering premature infants and 1.9 times at risk for delivering infants with low birth weight, compare to non anemic pregnant women.…”
Section: The Effect Of Nutritional Status Of Pregnant Women Toward Lomentioning
confidence: 99%
“…There are several reasons for continuing studies on this association: (i) the frequent overlapping of endemic zones for Schistosoma infection and undernutrition in Brazil and other emerging countries of the developing world, where at least 16% of the total population living in Africa, Asia and Latin America are under the risk of hunger (WFP 2006), (ii) the important role of nutrition in health, in low-income and middle-income countries, estimating that around 32% of the overall disease burden, in terms of mortality and morbidity, would be removed by eliminating malnutrition (Mason et al 2003), (iii) the concept of parasite-host-environment as interrelated subsystems, the host nutritional status being included in this context, (iv) the growing importance of the paradigm of the interaction of malnutrition and infection (Solomons 2007), (v) the urbanisation and appearance of new epidemiological profiles of schistosomiasis, emphasising the role of biological, social, economic, political and cultural determinants in the natural history of this helminthiasis, reflecting on the host nutritional status, (vi) the recognition of nutrition as a critical determinant of the immune response, epidemiological and clinical studies stressing that nutritional deficiencies alter immunocompetence (Chandra 1992), which further increase the risk and influence the outcome of infection (Meira 1995, Scrimshaw & SanGiovanni 1997, Fraker et al 2000, CunninghamRundles et al 2005, Landgraf et al 2007, Solomons 2007 and, finally, (vii) the need for a deeper evaluation on the real importance of nutrition in schistosome-infected hosts, in view of incomplete and sometimes contradictory results reported in the literature.…”
Section: Why Study Malnutrition In Association With Schistosome Infecmentioning
confidence: 99%
“…It can be defined as a state in which a deficiency of energy, protein, vitamins, and minerals causes measurable adverse effects on body composition, functions or clinical outcomes [1,2]. Every year, malnutrition contributes to the death of about 5.6 million children below 5 years of age and about 146 million children in developing worlds are under weight, anemic and at higher risk of early death [3][4][5][6]. Protein energy malnutrition results when the body is stressed from starvation and is not receiving the protein, energy fuel and micronutrients needed to sustain the metabolic process required for health and survival [7].…”
Section: Introductionmentioning
confidence: 99%